Study on the invitro synergistic susceptibility and biofilm inhibition mechanism of ceftazidime-avibactam combined with aztreonam against carbapenem-resistant Klebsiella pneumoniae - Guangfen Wang; Hui Zhang; Qiaoping Wu; Jianqiang Xu; Xuedan Qiu; Jinyuan Chen; Fujie Cui; Jian Zhou; Qingcao Li (Frontiers in Microbiology)
ObjectiveThis study aims to investigate the synergistic effects and biofilm inhibition mechanisms of ceftazidime-avibactam (CZA) combined with aztreonam (ATM) against carbapenem-resistant Klebsiella pneumonia (CRKP) commonly found in the local clinical setting, providing new insights for clinical anti-infective strategies.MethodsWe selected a total of 150 non-duplicate clinical isolates of CRKP from multiple hospitals in Ningbo. Common carbapenemase genes were detected using PCR. Broth microdilution and time-kill assays were used to evaluate the in vitro synergistic effects of CZA and ATM, both individually and in combination, on CRKP isolates with different enzyme types, and the fractional inhibitory concentration index (FICI) was calculated. The crystal violet staining method and bacterial cell permeability assay were employed to assess the impact of CZA, ATM, and their combination on the cell structure and biofilm formation capacity of CRKP. Real-time quantitative PCR (qRT-PCR) was used to measure the expression levels of biofilm-related genes (Luxs, mrkA, wbbM, pgaA, and wzm) in CRKP under treatment with CZA, ATM, or their combination.ResultsThe comparison of synergistic indices for different enzyme-type CRKP strains with CZA and ATM combination therapy showed a statistically significant difference (p < 0.01). The time-kill assay indicated that the time-kill curves for strains carrying blaKPC-2 and blaNDM-1 resistance genes were similar between the monotherapy and combination therapy groups, while the CZA + ATM combination therapy group showed a significant decrease in bacterial concentration after 4–8 h of cultivation compared to the CZA and ATM monotherapy groups. The crystal violet staining and bacterial cell permeability assays demonstrated that the CZA + ATM combination significantly reduced biofilm formation and increased cellular structure disruption in CRKP. The qRT-PCR results showed that CZA combined with ATM notably decreased the expression levels of biofilm-related genes Luxs, mrkA, wbbM, pgaA, and wzm in CRKP.ConclusionThe combination of ATM and CZA shows a strong synergistic antibacterial effect against CRKP strains with various enzyme types, with particularly notable synergy in strains carrying the blaKPC-2 resistance gene. Additionally, this combination significantly disrupts the cellular structure of CRKP and inhibits biofilm formation.